Recenzje - Szpak, Ewelina (Polska 1944/45-1989. Studia i Materiały, 2022)
Katarzyna Stańczak-Wiślicz, Piotr Perkowski, Małgorzata Fidelis, Barbara Klich-Kluczewska, Kobiety w Polsce 1945–1989. Nowoczesność Równouprawnienie Komunizm